Reflecting on teaching together and alone: preservice teachers’ processes of knowledge construction in writing and discussion - Hartmann, Ulrike; Kindlinger, Marcus; Trempler, Kati; Molitor, Anna-Lena; Fives, Helenrose (Frontiers in Education, 2025)
Understanding how preservice teachers (PSTs) engage with knowledge of educational sciences through reflective practice is critical to improving teacher education. This study investigates how PSTs construct knowledge when analyzing a complex classroom situation and explores how a reflective task format—individual essay writing or collaborative group discussion—shapes the types and quality of knowledge construction processes involved. Drawing on frameworks of reflective practice and epistemic cognition, we developed a coding scheme to identify five knowledge construction processes and three levels of implementation quality. Using data from a university-based teacher education course, we applied this scheme to PSTs’ written essays and transcribed group discussions. Our findings indicate that collaborative discussions elicited a broader variety of knowledge construction processes and deeper levels of implementation, while essays involved more references to scientific literature but fewer exploratory hypotheses. These results suggest that different reflective tasks afford distinct opportunities for preservice teachers to mobilize and integrate educational sciences knowledge. The study highlights how the perceived relevance and applicability of theoretical content are shaped not only by individual cognition but also by the task design and social context of reflection. Implications for teacher educators include selecting reflection formats strategically to support meaningful engagement with educational knowledge in preparation for complex pedagogical reasoning.